ENVIRONMENTAL LAW ENFORCEMENT IN INDONESIA FACING THE ERA OF GLOBALIZATION - Nita Nurvita; Detania Sukaraja (Academic Solution Publisher, 2024)
The process of globalization is marked by the rapid development of capitalism, which is increasingly open and globalizing the role of markets, investment and production processes of transnational companies which are then strengthened by ideology and a new world order of trade under a rule set by a global free trade organization, as an example of globalization is the increasing development of companies. The type of legal research that the author uses in the preparation of this legal writing is normative juridical research type. the obligation for everyone to maintain the ability of the environment so that it can continue to be utilized for the protection and needs of humans or other living things. Geographically, Indonesia is a very strategic part of efforts to realize a good environment for the world as a whole. This provides awareness that Indonesia must also comply with international law. Not only those issued by international institutions. This includes the collective agreement of the world community on efforts that are concretely dedicated to the preservation of the world's environment and even the universe. In fact, while natural resources do bring a major contribution to development, on the other hand, the sustainability of the availability of natural resources is ignored.